Fenomena “Career Cushioning” di Kalangan Gen Z: Motivasi dan Dampaknya terhadap Loyalitas Karyawan - Kurniawan, Agung Widhi (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
The phenomenon of career cushioning Gen Z employees' strategies in preparing career alternatives amid job uncertainty has become a global trend, but has not been widely studied in the context of local Indonesian startups. This qualitative research aims to reveal the motivation and impact of career cushioning on Gen Z employee loyalty in a startup company in Makassar City. Data were collected through in-depth interviews with 15 Gen Z employees (20-27 years old) and analysis of supporting documents, then thematically analyzed. The results show that career cushioning is driven by external (startup instability, economic pressure) and internal (desire for self-development) factors, with diverse forms such as side hustle, skills training, or personal branding. Its impact on loyalty is dynamic: in companies with a flexible culture, the practice strengthens commitment; conversely, in restrictive environments, it becomes a stepping stone to exit. The study concludes that career cushioning represents a transformation in the meaning of loyalty among Gen Z from traditional compliance to value-based reciprocity. The practical implication is that companies need to adopt a more adaptive HR management model by integrating career cushioning into employee development strategies.